FINITE ELEMENT ANALYSIS OF A LARGE FIXED TUBESHEET HEAT EXCHANGER BASED ON SUB-MODEL TECHNIQUE - LIU Bin; LIU XianPing; DONG JunHua; GAO BingJun (Jixie qiangdu)
As enormous number of tubes in large fixed tubesheet heat exchangers, it is difficult to model all the tubes and tubesheet connections in detail for FEA. Therefore, it fails to yield an accurate stress field around the connecting region of tubes and tubesheet, which is essential for the effective stress intensity evaluation. Taking a large fixed tubesheet heat exchanger as example, the maximum stress intensity location is found for the tube layout region of the tubesheet according to the coarse model. Then the sub model is utilized in the predetermined maximum stress location. In the sub model, detailed connecting structure of the tube and the tubesheet are included, such as the weld metal and contact condition between the tube and tubesheet hole. Both stress classification and limit load analysis are preformed for the sub model structure. Although both the weld and the tube fail the evaluation based on stress classification, it is more reasonable to evaluate the connecting region with the direct route based on limit load analysis for the structure with non axisymmetric stress distribution. Limit analysis is carried out and limit load is determined by zero-curvature method. It is shown that the structure meets the strength requirement based on the relevant standards.